2012
DOI: 10.7314/apjcp.2012.13.7.3501
|View full text |Cite
|
Sign up to set email alerts
|

CHEK2 1100delC Variant and Breast Cancer Risk in Caucasians: A Meta-analysis Based on 25 Studies with 29,154 Cases and 37,064 Controls

Abstract: Links between the CHEK2 1100delC heterozygote and breast cancer risk have been extensively explored. However, both positive and negative associations with this variant have been reported in individual studies. For a detailed assessment of the CHEK2 1100delC heterozygote and breast cancer risk, relevant studies published as recently as May 2012 were identified using PUBMED and EMBASE and selected using a priori defined criteria. The strength of the relationship between the CHEK2 1100delC variant and breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…NBN (Nijmegen breakage syndrome) has been shown to be associated with 3 fold increased risk for breast cancer in carriers of a 5-bp deletion (Bogdanova et al, 2008). Other Intermediate risk genes include RAD50, CHEK2, BRIP1, PALB2, FANCD1 and ATM (Ripperger et al, 2009;Yang et al, 2012). These genes have been associated with an odds ratio above 2, when there is a heterozygous germline mutation.…”
Section: Introductionmentioning
confidence: 99%
“…NBN (Nijmegen breakage syndrome) has been shown to be associated with 3 fold increased risk for breast cancer in carriers of a 5-bp deletion (Bogdanova et al, 2008). Other Intermediate risk genes include RAD50, CHEK2, BRIP1, PALB2, FANCD1 and ATM (Ripperger et al, 2009;Yang et al, 2012). These genes have been associated with an odds ratio above 2, when there is a heterozygous germline mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis by Yang et al . confirmed the significant association between the CHEK2 1100delC variant and female breast cancer risk, particularly in familial breast cancer cases among Caucasians [ 5 ].…”
Section: Introductionmentioning
confidence: 60%
“…Several breast cancer susceptibility genes, such as BRAC1, BRAC2 [43] and CHEK2 [44], [45], have been detected in recent decades. Additionally, Conlon et al [46] suggested that the effect of smoking on breast cancer may be differentially modified by the N-acetyltransferase 2 (NAT2) phenotype.…”
Section: Discussionmentioning
confidence: 99%